Microplastics as Emerging Contaminants and Human Health: Exploring Functional Nutrition in Gastric–Colon–Brain Axis Cancer - Maria Scuto; Cinzia Maria Grazia Lombardo; Bruna Lo Sasso; Eleonora Di Fatta; Raffaele Ferri; Angela Trovato Salinaro (Toxics, 2025)
Microplastics (MPs), emerging contaminants of significant global concern, have a substantially increased environmental impact due to their biological persistence and accumulation in the body. Exposure to MPs has been associated with oxidative stress, systemic inflammation, and cellular dysfunction, notably affecting critical tissues such as the stomach, colon, and brain. This review explores the correlation between MPs and cancer risk along the gastric–colon–brain axis, identifying the signaling pathways altered by MP exposure. Furthermore, it highlights the role of functional nutrition and bioactive flavonoids—including chlorogenic acid, coumaric acid, and naringin—as well as the use of highly bioavailable combined polyphenol nanoparticles as potential detoxifying agents. Functional nutrients are effective in enhancing cellular resilience against reactive oxygen species (ROS) production and MP-induced toxicity, offering protective effects at the gastric, intestinal, and brain barriers. Activation of the Nrf2 pathway by bioactive compounds promotes the expression of detoxifying enzymes, suggesting a promising nutritional strategy to mitigate MP-related damage. This review underscores how functional nutrition may represent a viable therapeutic approach to reduce the harmful effects of MP exposure. The integration of advanced technologies—such as microfluidic systems, organ-on-a-chip platforms, and machine learning—and the identification of key molecular targets lay the foundation for developing preventive and personalized medicine strategies aimed at lowering the risk of environmentally induced carcinogenesis.